Effect of Pd particle size on activity and cis-trans selectivity in partial hydrogenation of soybean oil-derived FAMEs over Pd/SiO2 catalysts - Numwong, Natthida; Prabnasak, Panisa; Prayoonpunratn, Patsakol; Triphatthanaphong, Pholawat; Thunyaratchatanon, Chachchaya; Mochizuki, Takehisa; Chen, Shih Yuan; Luengnaruemitchai, Apanee; Sooknoi, Tawan (My University, 2020)
Partial hydrogenation of soybean oil-derived fatty acid methyl esters (FAMEs) was performed to improve oxidative stability of biodiesel. The reaction was tested in a semi-batch reactor at 100 °C, 0.4 MPa. The effect of Pd particle size on activity and cis-trans selectivity was investigated over SiO2- and MCM-41-supported Pd catalysts, with different Pd loadings (0.5 and 1 wt.%). For Pd/SiO2 catalysts with relatively large Pd particle sizes (6.1–7.8 nm), the adsorption of polyunsaturated C18:2 and C18:3 FAMEs was promoted on the flat metal surface, providing 2- to 3-fold higher turnover frequency (TOF) compared with Pd/MCM-41 catalysts. In contrast, the Pd/MCM-41 catalysts with relatively small Pd particle sizes (2.7–4.0 nm), showed higher selectivity towards the desired monounsaturated C18:1 FAMEs due to lower affinity of isolated double bond (presented in C18:1) on the Pd surface. In addition, selectivity towards the desired cis-C18:1 FAMEs was found to be highly sensitive to Pd particle size. The 0.5Pd/MCM-41 catalyst with small Pd particle size (2.7 nm), provided high cis-C18:1 selectivity, resulting in a biodiesel with better cold flow property compared with the trans-isomers. With partial hydrogenation over the prepared Pd catalysts, biodiesel with significantly improved oxidative stability (>10 h) could be obtained.
Keywords: cis-trans selectivity; Fatty acid methyl ester; Oxidative stability; Partial hydrogenation; Particle size; Pd/SiO2 catalyst